Generation Z Cashless Preferences In The Post Covid-19 Pandemic Era: Identifying The Continuity Of Digital Payment Usage - Sholihah, Erlinda; Ariyani, Diyah (Universitas Muria Kudus, 2023)
This quantitative study aims to identify factors affecting the intention of continuity of digital payment use in Generation Z in the post-Covid-19 pandemic. Based on the concepts of ECM (Expectation Confirmation Model) and TAM (Technology Acceptance Model), perceived ease of use, usefulness, and satisfaction were selected as determining variables. Data were collected through questionnaires from 150 Generation Z respondents as digital payment users and tested based on the SEM-PLS technique using SmartPLS software version 4.0. This research has proven that perceived ease of use and satisfaction are the main factors for the continuance intention of digital payment use in Generation Z, especially in the post-Covid-19 pandemic. In contrast, perceived usefulness is not a significant predictor that affects the continuance intention of use. The results of this study are expected to contribute to the expansion of literacy and increase the development of digital payment systems to meet consumer needs in the current cashless era. Further research is needed in describing the continuance intention of digital payment use in Generation Z by adding more variables and increasing the sample to get better findings.